67.9k views
0 votes
PLZ HELP ME,!!!
.....​

PLZ HELP ME,!!! .....​-example-1

1 Answer

5 votes

6x-3y=63

Simplifying

6x + -3 = 63

Reorder the terms:

-3 + 6x = 63

Solving

-3 + 6x = 63

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.

-3 + 3 + 6x = 63 + 3

Combine like terms: -3 + 3 = 0

0 + 6x = 63 + 3

6x = 63 + 3

Combine like terms: 63 + 3 = 66

6x = 66

Divide each side by '6'.

x = 11

Simplifying

x = 11

User Ryan Ore
by
5.1k points